More than a “Petty Chief”: Understanding Fijian Chiefship through the Entrance Ceremony and Local History - Lin, Hao-Li (Anthropologica, 2020)
The diverse nature of Fiji’s chiefship and how its supremacy was strengthened by colonialism have already been closely examined. However, few studies have focused on village chiefs, who have limited authority and are at the lower end of regional chiefly hierarchies. Using both historical and ethnographic materials from a Fijian village, I argue here that its “petty chief,” as the role was called by nineteenth-century Westerners, is a powerful linkage to a past of stability represented by the chiefly title. This is particularly important for communities that have experienced historical turbulence. In this case study, it was mainly the measles crisis that caused population decline. The linkage is materialised by a standardised entrance ceremony in which the chiefly title is routinely acknowledged by foreign visitors through offerings (i-sevusevu) and thus elevated to a symbol that holds the community together. I also argue that the entrance ceremony that we observe today may have been prompted by Western contact. Through the analysis of the ceremony and local history, this study shows that the power of “petty chiefs” should be understood not solely by the structure of hierarchy, but also by their significance to historically turbulent communities.